Perceptions of Legitimacy: The Sex of the Legal Messenger and Reactions to Sexual Harassment Training. Issue 1 (24th March 2014) - Tinkler, Justine; Gremillion, Skylar; Arthurs, Kira
<x xml:space="preserve">Abstract</x> Research shows that exposure to sexual harassment policy sometimes activates traditional gender stereotypes. This article examines whether the sex of the legal messenger moderates reactions to the enforcement of sexual harassment laws. We employ a 2 × 2 experimental design in which we measure the effect of a sexual harassment policy intervention on male participants' gender beliefs. The design varies whether the person communicating the policy information is male or female. We find that female policy trainers activate implicit gender stereotypes, but explicit gender egalitarian beliefs. Other than improving men's perceptions of women's considerateness, the policy has little effect on beliefs in the conditions with a male trainer. These results suggest that the effect of law on social change is contingent on characteristics of the legal messengers. Findings contribute to our understanding of gender inequality and legitimacy processes and have practical implications for implementing effective policy.